All-Cause and Cause-Specific Mortality Rates of Patients Treated for Alcohol Use Disorders: A Meta-Analysis. Issue 4 (October 2018) - Abdul-Rahman, Abdul-Kareem; Card, Timothy R.; Grainge, Matthew J.; Fleming, Kate M.
Background: Although alcohol use disorders (AUDs) are known to increase the relative risk of all-cause and some cause-specific mortality, the absolute mortality rates of the AUD population are unknown. Such knowledge would benefit planners of the provision of services for this population, including in prioritizing the identification and/or treatment of diseases likely to cause their death. Methods: We conducted a systematic review of studies in English, reporting the cause-specific mortality rates among people treated for AUDs. Number of deaths by cause and total person-years of follow-up were extracted. All-cause and cause-specific mortality rates per 1000 person-years were meta-analyzed assuming random effects. Results: Thirty-one studies were included. Participants were mainly middle-aged males. The quality of studies was generally good. A total of 6768 all-cause deaths in 276, 990.7 person-years of follow-up (36, 375 patients) were recorded, and the pooled all-cause mortality rate was 27.67/1000 person-years (py) (95% confidence interval [CI]: 23.9, 32.04). The most common cause of death in the AUD population was cardiovascular disease (CVD) (6.9/1000 py; 95% CI: 5.61, 8.49), followed by gastrointestinal deaths (5.63/1000 py; 95% CI: 4.1, 7.74), unnatural deaths (4.95/1000 py; 95% CI: 4.01, 6.09)), neoplasms, respiratory diseases, and substance use disorders. Conclusions: Patients with AUDs have increased rates of all-cause and cause-specific mortality compared with the general population. Like the general population, they are most likely to die of CVD. In contrast to the general population, gastrointestinal and unnatural deaths are the next most common causes of death. We believe these facts should be considered when planning health care services for patients with AUDs.